Tempered Forming of Magnesium Alloys Using the Example of Roll Forming. (2015) - Richter, K.; Haase, R.; Schieck, F.; Landgrebe, D.
Abstract: The sheet metal forming of magnesium alloys requires an adaption of the forming processes utilized. Due to limited formability at room temperature, heating above a temperature of 200 to 225 °C is necessary in order to activate additional gliding planes. By the example of roll forming, the temperature regime and implementation of heating equipment into the forming process is illustrated. On account of the progressive feed of sheet material necessary for roll forming, a transverse flux induction heating was used in the experimental setup. Results of experimental design and experimentation with AZ31 alloy will be presented in this paper.